Changes in soil properties of four agro-ecological zones of Tangail district in Bangladesh - Kumar, U; Mukta, M; Mia, MY (Progressive Agriculture, 2019)
This study was undertaken to investigate the changes in status of soil properties in four AEZs (AEZ 28, AEZ 9, AEZ 8 and AEZ 7) of Tangail district in Bangladesh over the span of the years. In 2017, the pH value of four AEZ was ranged from strongly acidic to slightly acidic but before 2000 it was strongly acidic to slightly alkaline. The present OM status was medium and before 2000 it was also medium. The present N status was very low, low, low and low, respectively but before 2000 it was low, medium, low and low, respectively. The present P status was low, low, low and very low, respectively in upland and low in wetland but before 2000 it was medium, medium, low and medium in upland and optimum, medium, medium and optimum in wetland, respectively. The present K status was medium, low, low and low in upland and medium, low, low and low in wetland, respectively but before 2000 it was optimum, high, high and optimum in upland and high, very high, very high and optimum in wet land, respectively. Under upland and wetland, the present S status was low, low, very low and low, respectively but before 2000 it was medium in all AEZ. The present Ca status was medium, medium, optimum and optimum, respectively but before 2000 it was optimum, high, high and high, respectively. The present Mg status was high, high, very high and very high, respectively but before 2000 it was medium in all AEZ. The Present Zn status was optimum, medium, low and low, respectively but before 2000 it was medium very high, very high, very high and optimum, respectively. The present B status was low in all AEZ but before 2000 it was optimum, optimum, low and low, respectively. With few exceptions, the nutrient status of the study area was reducing day by day and it was less than optimum level which was not suitable for sustainable crop production. Progressive Agriculture 29 (4): 284-294, 2018